Quotation does not need marks of quotation - De Brabanter Philippe (Linguistics, 2023)
Two major types of quotation theories can be distinguished according to whether they regard marks of quotation as necessary (type-1) or not necessary (type-2) for quotation. I argue that taken at face value, the empirical evidence disqualifies type-1 theories. I then show that even if we accept that surface appearances can be deceptive – ‘unmarked’ quotations are simply not quotations, or absent marks are underlain by marks in hidden syntactic structure – type-1 theories still prove inadequate. By contrast, a particular form of type-2 theory, depiction theory, is consistent with the empirical evidence, proves compatible with syntactic analyses that posit a covert quotative operator, and is equipped to account for the grammatically deviant behavior of certain categories of quotations.